The political theory of the Irish Constitution : Republicanism and the basic law - Daly, Eoin; Hickey, Tom (Law teacher) (Manchester Political Studies, 2015)
Recent years have witnessed a revived interest in civic republicanism in Ireland, in tandem with a growing consciousness of republican ideas across the English-speaking world. Yet while republicanism is posited as a catch-all public philosophy and as a framework for political reform in Ireland and elsewhere, its content remains highly ambiguous and contested. Its implications for constitutional structure and constitutional theory are the subject of wide debate in both legal and political thought. In this book, Eoin Daly and Tom Hickey consider republican themes in the Irish constitutional tradition.